2020
DOI: 10.4103/1735-5362.301336
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of antioxidant activity of some novel hydroxypyridinone derivatives: a DFT approach for explanation of their radical scavenging activity

Abstract: Background and purpose: Reactive oxygen species (ROSs) are continuously produced as byproducts of cell metabolism. Free radicals are an unstable form of ROSs with the tendency to react readily with biomolecules such as amino acids, lipids and DNA. These reactions lead to oxidative damages to the cell. Oxidative stress occurs when the concentration of the ROSs exceeds the capacity of antioxidative protection systems of the body. 5-Hydroxypyridin-4-one derivatives can chelate Fe 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Furthermore, they exhibited good antioxidant ability, as reported in our previous manuscript. [19] Docking pose analysis of these compounds into the active site of AChE demonstrated that they behave like donepezil. Indeed, 5-hydroxypyridine-4-one moiety behaves similar to the ketone group of indanone moiety of donepezil to interact with active site gorge of AChE.…”
Section: Molecular Docking Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they exhibited good antioxidant ability, as reported in our previous manuscript. [19] Docking pose analysis of these compounds into the active site of AChE demonstrated that they behave like donepezil. Indeed, 5-hydroxypyridine-4-one moiety behaves similar to the ketone group of indanone moiety of donepezil to interact with active site gorge of AChE.…”
Section: Molecular Docking Resultsmentioning
confidence: 99%
“…Furthermore, when this scaffold is added to AChE inhibitor while bearing hydroxy moiety at C-5 position of pyridin-4-one ring, it confers good antioxidant and metal chelation abilities in designing compounds. [19] In another fascinating aspect, hydroxypyridin-4-one scaffold which contains benzyloxy moiety at C-5 position of pyridin-4-one ring can play a role similar to the benzylpiperidine scaffold for interaction with the active site gorge amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals with iron chelating ability can potentially suppress oxidative stress to alleviate the destroying effects of the free radicals [21] . A prospective strategy for delivering new antioxidants may be a chemical compound with dual functionality – iron chelation to prevent Fenton and Haber‐Weiss reactions and the ability to scavenge radicals [22–25] …”
Section: Introductionmentioning
confidence: 99%
“…Two strategies are usually used to investigate mechanisms of antioxidant activity. The first strategy uses vertical energies, which are based on the difference of total electronic and thermal enthalpies [23] . The second consists of the frontier orbital calculations, which computes the difference between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies of the neutral molecules, and is known as the orbital vertical method [50] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation